2022
DOI: 10.3390/ijms23158156
|View full text |Cite
|
Sign up to set email alerts
|

Photoreceptor Cells Constitutively Express IL-35 and Promote Ocular Immune Privilege

Abstract: Interleukin-27 is constitutively secreted by microglia in the retina or brain, and upregulation of IL-27 during neuroinflammation suppresses encephalomyelitis and autoimmune uveitis. However, while IL-35 is structurally and functionally similar to IL-27, the intrinsic roles of IL-35 in CNS tissues are unknown. Thus, we generated IL-35/YFP-knock-in reporter mice (p35-KI) and demonstrated that photoreceptor neurons constitutively secrete IL-35, which might protect the retina from persistent low-grade inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…A considerable decrease of IL-35 (attributed to the massive death of photoreceptor cells) preceded the extravasation of proinflammatory Th1/Th17 lymphocytes into the retina, which eventually led to the onset and exacerbation of uveitis in p35-KI mice. Although the loss of IL-35 protective effects and inflammation-induced death of photoreceptors resulted in the exacerbation of uveitis, this study indicates that constitutive IL-35 secretion in the retina may be linked to functions that promote sterilisation immunity in the neuroretina, contributing to the maintenance of ocular immune privilege [86].…”
Section: Pathogenetic Insights From Experimental Studiesmentioning
confidence: 75%
See 1 more Smart Citation
“…A considerable decrease of IL-35 (attributed to the massive death of photoreceptor cells) preceded the extravasation of proinflammatory Th1/Th17 lymphocytes into the retina, which eventually led to the onset and exacerbation of uveitis in p35-KI mice. Although the loss of IL-35 protective effects and inflammation-induced death of photoreceptors resulted in the exacerbation of uveitis, this study indicates that constitutive IL-35 secretion in the retina may be linked to functions that promote sterilisation immunity in the neuroretina, contributing to the maintenance of ocular immune privilege [86].…”
Section: Pathogenetic Insights From Experimental Studiesmentioning
confidence: 75%
“…Yu et al [86] provided evidence that the cytokine IL-35 is involved in the pathogenesis of uveitis. They generated IL-35/YFPknock-in reporter mice (p35-KI) and showed that IL-35 is constitutively produced by photoreceptor neurons [86]. This might prevent impairment of photoreceptors following persistent lowgrade inflammation.…”
Section: Pathogenetic Insights From Experimental Studiesmentioning
confidence: 99%
“…IL-12Rβ2 is expressed on the surface of activated T cells, NK cells, B cells, and dendritic cells [ 15 , 16 , 17 , 18 ]. The IL-12Rβ2 subunit is undetectable on naive resting CD4+ T cells but its expression may be significantly altered by different molecules.…”
Section: Receptor and Signaling Pathway Of Il-35mentioning
confidence: 99%
“…Interestingly, unlike transforming growth factor-β (TGF-β), which is constitutively expressed, IL-35 is suggested to be expressed in human tissues in response to inflammation [ 11 ]. However, a recent study on mice models has revealed that IL-35 is constitutively produced by cells in the retina, including the photoreceptor rod cells and the cone cells, which indicate that its housekeeping functions maintain ocular immune privilege [ 15 ].…”
Section: Introductionmentioning
confidence: 99%